THE IMPACT OF EDUCATION ON ECONOMIC GROWTH IN INDONESIA - Faizal Reza; Tri Widodo (Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
Does education promote economic growth? The aim of this study is to find out the impact of education on economic growth in Indonesia. This research employed panel data technique to investigate the relationship between education and economic growth in Indonesia during the period 1996-2009. The empirical results show that education per worker has a positive and significant impact on economic growth. The estimates of panel model suggest that a 1% increase in average education per worker will lead to about 1.56% increase in output. By using instrument analysis, researchers found that Jawa Timur is a province with highest economic growth in Indonesia. In contrast, Bengkulu experiences the lowest position with the lowest economic growth. The results show us that there are still substantial disparities within the provinces in Indonesia.